Rib Presence, Anterior Rib Cage Integrity, and Segmental Length Affect the Stability of the Human Thoracic Spine: An in vitro Study - Liebsch, Christian; Wilke, Hans-Joachim (Frontiers in Bioengineering and Biotechnology, 2020)
The effects of segmental length as well as anterior rib cage and costovertebral joint integrity on thoracic spinal stability have not been extensively investigated, but are essential for the calibration and validation of numerical models of the thoracic spine and rib cage. The aim of the study was to quantify these effects by in vitro experiments. Eight human thoracic spine specimens (C7-L1) including the rib cage were loaded with pure moments of 5 Nm in flexion/extension, lateral bending, and axial rotation while tracking the motions of all functional spinal units. Specimens were tested stepwise in four different conditions: (1) In the intact condition, (2) after cutting all anterior rib-to-rib connections, (3) after partitioning the polysegmental specimens into monosegmental specimens, and (4) after removing the ribs in the monosegmental condition. Significant increases of the range of motion (p < 0.05) were especially found at the segmental levels of the upper half of the thoracic spine in all motion planes and for all resection steps, particularly in axial rotation, while the stabilizing effects of the structures decreased in inferior direction. Partitioning of polysegmental specimens into monosegmental specimens primarily affected the stability in lateral bending, while the effects of resection were generally lowest in flexion/extension. Presence of the ribs, anterior rib cage integrity, and segmental length all affect the thoracic spinal stability and have therefore to be considered in the calibration process of numerical models of the thoracic spine and rib cage.